قلب کی ظاہری اور باطنی ماہیت: قرآن و سنت اور سائنس کی روشنی میں تجزیاتی مطالعہ: The External and Internal Nature of the Heart: An Analytical Study in the Light of the Quran, Sunnah, and Science - Hafiz Muhammad Usman (Correspondent Author); Dr. Manzoor Ahmad (International Research Journal of Arabic and Islamic Studies, 2024)
There is so much depth in the teachings of Islam that it considers the heart as more than just a human organ. The importance of the heart in Islam cannot be underestimated. It is a spiritual heart that has a deep intelligence and wisdom. The heart is addressed in the Qur'an as a processor of information, especially about sincerity. Regarding the heart, this address draws attention to the relationship between heart and intention. In the Qur'an and Hadith, the human heart is described as the source of intelligence and the organ that holds emotions and feelings. In the middle of the 20th century, science for the first time made this amazing discovery that the cells of intelligence similar to the human brain are found in the human heart. There have also been many important scientific researches. These researches will be briefly presented in this discussion so that we can understand that science today is discovering the facts that the Qur'an and Hadith had described 1400 years ago.